Pengaruh Model Pembelajaran Self Directed Learning (SDL) Terhadap Kemampuan MenulisTeks Anekdot Siswa Kelas X SMK Negeri 1 Lubuk Pakam - Ramadhani, Putri Suci; Deliani, Susy; Muliatik, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to determine the significant effect of the use of the Self Directed Learning Model on the ability to write anecdotal texts of class X students of SMK Negeri 1 Lubuk Pakam. The type of research used is quantitative research with a two group pretest-posttest design. The population in this study were 68 class X students of SMK Negeri 1 Lubuk Pakam. The instrument in this study the researcher used a test. Based on the results of the study, the ability to write anecdotal texts before using the Self Directed Learning learning model obtained an average of 55 and a standard deviation of 12.90994 with a distribution of pre-test data tendencies included in the poor category. The ability to write anecdotal texts after using the Self Directed Learning learning model averaged 83.1 and a standard deviation of 7.021396 with a distribution of post-test data tendencies included in the very good category. Based on the results of the hypothesis testing, tcount>ttable (10.828>2.03452) was obtained. This means that Ho is rejected and Ha is accepted, which means that there is an influence of the Self Directed Learning learning model on the ability to write anecdotal texts in class X students of SMK Negeri 1 Lubuk Pakam.